Interaction of periodontitis and orthodontic tooth movement—an in vitro and in vivo study - Rath-Deschner, Birgit; Nogueira, Andressa V. B.; Beisel-Memmert, Svenja; Nokhbehsaim, Marjan; Eick, Sigrun; Cirelli, Joni A. [UNESP]; Deschner, James; Jäger, Andreas; Damanaki, Anna (Springer Nature, 2021)
Objectives: The aim of this in vitro and in vivo study was to investigate the interaction of periodontitis and orthodontic tooth movement on interleukin (IL)-6 and C-X-C motif chemokine 2 (CXCL2). Materials and methods: The effect of periodontitis and/or orthodontic tooth movement (OTM) on alveolar bone and gingival IL-6 and CXCL2 expressions was studied in rats by histology and RT-PCR, respectively. The animals were assigned to four groups (control, periodontitis, OTM, and combination of periodontitis and OTM). The IL-6 and CXCL2 levels were also studied in human gingival biopsies from periodontally healthy and periodontitis subjects by RT-PCR and immunohistochemistry. Additionally, the synthesis of IL-6 and CXCL2 in response to the periodontopathogen Fusobacterium nucleatum and/or mechanical strain was studied in periodontal fibroblasts by RT-PCR and ELISA. Results: Periodontitis caused an increase in gingival levels of IL-6 and CXCL2 in the animal model. Moreover, orthodontic tooth movement further enhanced the bacteria-induced periodontal destruction and gingival IL-6 gene expression. Elevated IL-6 and CXCL2 gingival levels were also found in human periodontitis. Furthermore, mechanical strain increased the stimulatory effect of F. nucleatum on IL-6 protein in vitro. Conclusions: Our study suggests that orthodontic tooth movement can enhance bacteria-induced periodontal inflammation and thus destruction and that IL-6 may play a pivotal role in this process. Clinical relevance: Orthodontic tooth movement should only be performed after periodontal therapy. In case of periodontitis relapse, orthodontic therapy should be suspended until the periodontal inflammation has been successfully treated and thus the periodontal disease is controlled again.
Keywords: Fusobacterium nucleatum; Orthodontic tooth movement; Periodontitis; Periodontium